Metastatic Pancreatic Cancer: Are We Making Progress in Treatment? - Joanne Chiu; Thomas Yau (Gastroenterology Research and Practice)
Development of systemic treatment for advanced pancreatic cancer (APC) has been challenging. After fluorouracil, gemcitabine (GEM) became the treatment of choice based on its benefit of symptom relief. Many cytotoxic agents have been combined with GEM in search of regimens with improved survival benefit. However, there were only marginal benefits in people with good performance status. Recently, the combination regimen consisting of oxaliplatin, irinotecan, fluorouracil, and leucovorin (FOLFIRINOX) was found to achieve unprecedented survival benefit and has become the preferred option for patients with good clinical conditions. On the other hand, many biological agents have been combined with GEM, but only erlotinib was found to derive statistically significant survival advantage. However, the effect was too small to be appreciated clinically. The effort in development of targeted therapy in APC continues. This paper summarized key findings in the development of chemotherapy and targeted therapy for APC patients and discussed future directions in management.